2020
DOI: 10.3390/ma13184185
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Ti6Al4V Alloy Used in Dental Implants Immersed in Streptococcus gordonii and Fusobacterium nucleatum Solutions

Abstract: The titanium alloy, Ti6Al4V, is used in dentistry for dental implants because of its excellent resistance to corrosion and its high biocompatibility. However, periimplantitis is considered the main reason for treatment failure. The Ti6Al4V alloy was used to study the corrosion behavior for dental implant applications, using an experimental arrangement of three electrodes with the bacteria Streptococcus gordonii and Fusobacterium nucleatum, in addition to Ringer’s lactate as electrolytes, at 37 °C and a pH of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The sulfides produced by P. gingivalis did not cause titanium corrosion for 14 days. De la Garza-Ramos [ 24 ] showed a greater corrosion rate in Ti6Al4V alloy at 4 days of exposure by the medium that contains the Streptococcus gordonii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfides produced by P. gingivalis did not cause titanium corrosion for 14 days. De la Garza-Ramos [ 24 ] showed a greater corrosion rate in Ti6Al4V alloy at 4 days of exposure by the medium that contains the Streptococcus gordonii .…”
Section: Discussionmentioning
confidence: 99%
“…The coatings may have decreased the surface roughness by covering and filling remaining scratches and irregularities of the surface. De la Garza-Ramos [ 24 ] indicated that morphology does not present localized corrosion in the Ti6Al4V alloy by SEM observations in contact with Fusobacterium nucleatum and Streptococcus gordonii .…”
Section: Discussionmentioning
confidence: 99%
“…Both early (e.g., S. mutans, Streptococccus gordonii (S. gordonii), and Lactobacilli) and late (e.g., P. gingivalis) colonizers and the bridging organisms (e.g., Fusobacterium nucleatum (F. nucleatum)) of the oral biofilm cause corrosion [16,[46][47][48].…”
Section: Oral Biofilmmentioning
confidence: 99%
“…Contrarily, exposure of Ti6Al4V alloy to the electrolyte solution containing S. gordonii with or without F. nucleatum showed a reduced corrosion rate due to the formation of a passive TiO 2 film by these bacteria. However, at 96 hours, the electrochemical potential of the solution of F. nucleatum with S. gordonii was altered with an increased tendency towards corrosion [47].…”
Section: Oral Biofilmmentioning
confidence: 99%
See 1 more Smart Citation